(untitled) (Cultura Económica, 2021)
In this article I propose to point out some important affinities between Carl Schmitt and Augusto Del Noce. These two important catholic thinkers understood the profound relationship between atheism and technique. This topic is very interesting to understand the "spiritual" genesis of the "affluent society" and, above all, to understand an important aspect that has led to the affirmation of the ideology of neoliberalism. These topics are fundamental to current catholic philosophical thought, which after Vatican Council II has to confront Modernity.